(untitled) (International journal of artificial intelligence, 2025)
This article examines the laws of probability theory – formulas of addition and multiplication, their mathematical essence, areas of practical application and examples. These formulas are widely used in statistical analysis, economics, engineering, natural sciences, and information technology.